Gall Bladder Activity on Technetium99m-Ethylenedicysteine Renogram Masquerading as Ectopic Kidney - Aka, Sailaja (Indian J Nucl Med, 2019)
(99m)Tc-EC (Technetium-99m-ethylenedicysteine) is a renal tubular imaging agent introduced as an alternative to (99m)Tc-MAG3 (Technetium-99m-mercaptoacetyltriglycine) (1). This radiopharmaceutical can be easily labeled at room temperature and has high radiochemical purity and long stability for at least 8 h. Within 1 h 70% of (99m)Tc-EC is excreted in the urine (2). (99m)Tc-EC provides the same Scintigraphic information as (99m)Tc-MAG3. The Hepato biliary excretion of (99m)Tc-EC is very low and usually does not affect image interpretation on routine imaging, the possibility of visualization of the gall bladder should be kept in mind while reporting the 99mTc-EC renogram (1). We present a case of (99m)Tc-EC renogram, a suspected case of hypoplastic/ectopic right kidney, to look for ectopic kidney. In this case, there was unexpected visualization of gallbladder in delayed images. We herewith present this case, so that physician should be careful while reporting (99m)Tc-EC renogram, as there may be chances for gall bladder to be masquerading as Ectopic kidney.